Investigating the Relationship between Images and Text in First Grade Arabic Textbooks Based on the "Warsh and Mite" Classification - Amin Nazari Terizi; Fazllolah Mirghaderi (دراسات في اللغة العربيّة وآدابها)
Images are an important educational tool in textbooks because they play a significant role in enhancing student learning in the content of the book and also have a direct role in facilitating the teaching of the course content. Many researchers in the field of education pay close attention to the coherence between the images and the texts of the book because the more the relationship and coherence between images and text increase, the better the level of teaching and learning process will be. Therefore, the aim of the present study is to investigate the relationship between images and text of first grade Arabic textbooks based on three levels of "Warsh and Mite" classification. The present study population is all images of Arabic textbooks in the first year of high school, and the research sample consists of 470 images with text that have been purposefully selected; the research method is content analysis. Findings indicate that most of the images of Arabic books of the junior high school are related and coherent with the texts of the book with 85.74% of the cases. This is due to the authors' great attention to the importance of the relationship between image and text, given the significant effect of the coherence between images text in enhancing the process of interaction between teacher and students as well as improving their cognitive aspect; of these, 14.25% (equivalent to 67 images) cover incomplete text content. These images have a decorative function and do not have a positive effect on the understanding of educational texts. The reason can be found in the fact that these images are sometimes unclear or incomplete, so that only a small or simple part of the content of the text such as the characters of the text, the process of action and communication between the characters, places, icons, or signs are covered by these images.